Analisis Komposisi Fotografi Pre-Wedding Karya Jimmy Lukas Ditinjau dari Rule of Thirds - Ratih Angelia Silaban; Khaerul Saleh (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The rule of thirds is a compositional guide whose purpose is to create quality photos. This study aims to determine the composition of the Rule of thirds contained in Pre-wedding photos by Jimmy Lukas. This research was conducted from November to December 2021.  This study uses a qualitative descriptive method with a sample size of 10 works. In taking the research sample using the purposivetechnique sampling, namely Sampling is adjusted according to predetermined criteria and is considered to be in accordance with the needs of photo research. The results of this study indicate that pre-wedding photos by Jimmy Lukas reached a good category by achieving an average score of 81. Data assessment instrument. This research uses assessment parameter data. The analysis has complied with the composition of the Rule of Thirds and the elements of composition. In the discussion or analysis, it can be described that Jimmy Luke's work has complied with the composition of the  Rule of thirds and the compositional elements also create beautiful chemistry for the bride and groomphoto work inpre-wedding Jimmy Lukas.